Construction and application of a non-vomiting management mode in laminar flow ward for hematopoietic stem cell transplantation patients (造血干细胞移植患者层流舱内无呕管理模式的构建及应用) - SU JiLiang (苏继亮); SHAN Yuehua (单月华); ZHOU Ting (周婷) (Journal of International Translational Medicine Limited, 2024)
Objective To establish a non-vomiting management model of laminar flow ward for patients undergoing hematopoietic stem cell transplantation and analyze its clinical application effect, so as to reduce the incidence of nausea and vomiting and improve the quality of life of patients undergoing hematopoietic stem cell transplantation. Methods Based on the evidence, the non-vomiting management mode of laminar flow ward for hematopoietic stem cell transplantation patients was established by literature review, semi-structured interview and group discussion. Conveniently select 50 patients in the hematopoietic stem cell transplantation center from March 2022 to November 2022 as the control group, and adopt routine nursing intervention; From December 2022 to July 2023, 50 patients were taken as the observation group, and based on the nursing measures of the control group, the non-vomiting management mode of laminar flow ward without vomiting was applied to intervene. The grade of nausea and vomiting, functional life index of vomiting, anxiety and depression, and satisfaction level were compared between the two groups. Results Patients in the observation group had a lower degree of nausea and vomiting compared with those in the control group (Z=-2. 77, P＜0. 01). Scores of Functional Living Index-Emesis (FLIE ) in the observation group were higher than those in the control group on the 7th, 14th and 21st day after stem cell transfusion (P＜0. 01). Scores of Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDSS) in the observation group were lower than those in the control group on 7th after stem cell transfusion and one day before discharge from laminar flow ward(P＜0. 01). The score of patient satisfaction in the observation group was higher than that in the control group(t＝4. 89, P＜0. 01). Conclusion The non-vomiting management mode of laminar flow ward for patients undergoing hematopoietic stem cell transplantation is reasonable and feasible, which can reduce the incidence of nausea and vomiting, relieve patients' anxiety and depression, improve patients' satisfaction and improve their quality of life. (目的 构建造血干细胞移植患者层流舱内无呕管理模式并分析其临床应用效果, 以期降低造血干细胞移植患者恶心呕吐发生率, 提高生活质量。方法 基于循证, 采用文献查阅、半结构访谈、小组讨论等构建造血干细胞移植患者层流舱内无呕管理模式。便利抽取2022年3月-11月医院造血干细胞移植中心收治的50例患者作为对照组, 采用常规护理干预; 2022年12月-2023年7月收治的50例患者作为观察组, 在对照组的护理措施基础上应用构建的层流舱无呕管理模式进行干预。比较两组患者恶心呕吐分级、呕吐功能性生活指数(FLIE)量表评分、焦虑自评量表(SAS)评分、抑郁自评量表(SDS)评分和满意度。结果 观察组恶心呕吐的严重程度较对照组轻, 差异有统计学意义(Z=-2. 77, P＜0. 01)。回输干细胞第7天、第14天、第21天, 观察组(FLIE)量表评分高于对照组, 差异有统计学意义(P＜0. 01)。回输干细胞第7天和出舱前1天, 观察组SAS量表和SDS量表评分低于对照组, 差异有统计学意义(P＜0. 01)。观察组患者满意度得分高于对照组, 差异有统计学意义(t＝4. 89, P＜0. 01)。结论 造血干细胞移植患者层流舱内无呕管理模式合理、可行, 能有效降低患者恶心呕吐发生率, 缓解焦虑抑郁情绪, 改善移植期间的生活质量。)